Pengaruh Media Pembelajaran Berbasis Komputer Aplikasi Paint Terhadap Kemampuan Kognitif Anak Usia 4-5 Tahun di TK Aisyiyah Bustanul Athfal 22 Balongpanggang - Wiwit Widiawati Widiawati; Muhammad Busyro Karim; Dewi Mayangsari (Universitas Trunojoyo Madura, 2018)
The purpose of this study is determine the effect of computer based on the learning of media Paint application forward the cognitive abilities of children A2 TK Aisyiyah Bustanul Athfal 22 Balongpanggang Gresik. Media of learning is everything that is used by teacher to simplify the delivery of learning materials. The media is computer-based learning which has paint application that is used to stimulate the cognitive abilities of children, especially in aspects of learning and problem solving, logical thinking, and symbolic thinking. This research uses quantitative approach that is experimental method with Pre-experimental design research design type one-group pre-test post-test. The subject of this study is a group A children in kindergarten AisyiyahBustanulAthfal 22 Balongpanggang Gresik as many as 11 children. Techniques of collecting data of ths research is participant observation and documentation in the form of photos of activities and plans of daily learning. Data processing uses t-test data analysis. The result of data analysis obtained by Tcount value is -5,45 and Ttable value 2,086 then (-2,086 -5,45) and Ha accepted. Based on the data analysis shows there is a significant influence between computer-based learning media paint application to the cognitive abilities of children.